Nutritional and Functional Properties of Edible Mushrooms: A Food with Promising Health Claims - Viviana Loria-Kohen; Thais Lourenço-Nogueira; Isabel Espinosa-Salinas; Francisco R. Marín; Cristina Soler-Rivas; Ana Ramirez de Molina (Journal of Pharmacy and Nutrition Sciences, 2014)
Over the past two decades, there has been a steady flow of publications about the health effects related to mushrooms consumption. They represent a valuable source of protein, present high levels of fiber, some vitamins and minerals, and they also have reduced amount of fat and sodium. In addition, their complex carbohydrates profile can strengthen considerably the immune system. Edible mushrooms have been related to significant functional properties due to their bioactive compounds, such as eritadenine, phenolic compounds, sterols (as ergosterol), chitosan, etc., These substances are considered as important agents in the prevention and treatment of different health conditions like obesity, diabetes, or cardiovascular disease. However, it is important to remember that most of scientific studies are made in animal models and, therefore, some evidences regarding mushroom consumption have yet to be confirmed in clinical trials. Despite of the growing appeal for humans by their medicinal effects and nutritional value, mushrooms are also very appreciated for their texture, flavor, and versatility in culinary. They can be easily incorporated into any kind of dish, improving the dietary diversity without adding many calories. The information presented in this review point out that the positive effect of mushrooms on health is beyond basic nutrition. Therefore, it is very valuable expanding our knowledge about mushrooms, in order to identify all their active principles and the mechanisms involved in each health benefit, getting aware about the doses required to achieve that, in a safe range for humans.